Personalised eHealth intervention to increase physical activity and reduce sedentary behaviour in rehabilitation after cardiac operations: study protocol for the PACO randomised controlled trial (NCT03470246). Issue 1 (5th July 2019) - Vasankari, Ville; Halonen, Jari; Husu, Pauliina; Vähä-Ypyä, Henri; Tokola, Kari; Suni, Jaana; Sievänen, Harri; Anttila, Vesa; Airaksinen, Juhani; Vasankari, Tommi; Hartikainen, Juha
Abstract : Introduction: Personalized intervention to increase physical Activity and reduce sedentary behaviour in rehabilitation after Cardiac Operations (PACO) is a smartphone-based and accelerometer-based eHealth intervention to increase physical activity (PA) and reduce sedentary behaviour (SB) among patients recovering from cardiac surgery. Design: Prospective randomised controlled trial. Methods and analysis: The present protocol describes a randomised controlled clinical trial to be conducted in the Heart Centres of Kuopio and Turku university hospitals. The trial comprises 540 patients scheduled for elective coronary artery bypass grafting, aortic valve replacement or mitral valve repair. The patients will be randomised into two groups. The control group will receive standard postsurgical rehabilitation guidance. The eHealth intervention group will be given the same guidance together with personalised PA guidance during 90 days after discharge. These patients will receive personalised daily goals to increase PA and reduce SB via the ExSedapplication. Triaxial accelerometers will be exploited to record patients' daily accumulated PA and SB, and transmit them to the application. Using the accelerometer data, the application will provide online guidance to the patients and feedback of accomplishing their activity goals. The data will also be transmitted to the cloud, where a physiotherapist can monitor individual activity profiles and customise the subsequent PA and SB goals online. The postoperative improvement in patients' step count, PA, exercise capacity, quality of sleep, laboratory markers, transthoracic echocardiography (TTE) parameters and quality of life, and reduction in SB and incidence of major cardiac events are investigated as outcomes. Conclusions: The PACO intervention aims to build a personalised eHealth tool for the online tutoring of cardiac surgery patients. Trial registration number: NCT03470246 .